Insights Into the Emergence of Paroxysmal Nocturnal Hemoglobinuria - Colden, Melissa A.; Kumar, Sushant; Munkhbileg, Bolormaa; Babushok, Daria V. (Frontiers in Immunology, 2022)
Paroxysmal Nocturnal Hemoglobinuria (PNH) is a disease as simple as it is complex. PNH patients develop somatic loss-of-function mutations in phosphatidylinositol N-acetylglucosaminyltransferase subunit A gene (PIGA), required for the biosynthesis of glycosylphosphatidylinositol (GPI) anchors. Ubiquitous in eukaryotes, GPI anchors are a group of conserved glycolipid molecules responsible for attaching nearly 150 distinct proteins to the surface of cell membranes. The loss of two GPI-anchored surface proteins, CD55 and CD59, from red blood cells causes unregulated complement activation and hemolysis in classical PNH disease. In PNH patients, PIGA-mutant, GPI (-) hematopoietic cells clonally expand to make up a large portion of patients’ blood production, yet mechanisms leading to clonal expansion of GPI (-) cells remain enigmatic. Historical models of PNH in mice and the more recent PNH model in rhesus macaques showed that GPI (-) cells reconstitute near-normal hematopoiesis but have no intrinsic growth advantage and do not clonally expand over time. Landmark studies identified several potential mechanisms which can promote PNH clonal expansion. However, to what extent these contribute to PNH cell selection in patients continues to be a matter of active debate. Recent advancements in disease models and immunologic technologies, together with the growing understanding of autoimmune marrow failure, offer new opportunities to evaluate the mechanisms of clonal expansion in PNH. Here, we critically review published data on PNH cell biology and clonal expansion and highlight limitations and opportunities to further our understanding of the emergence of PNH clones.